2014
DOI: 10.1089/ars.2013.5683
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Liver X Receptor Improves Viability of Adipose-Derived Mesenchymal Stem Cells to Attenuate Myocardial Ischemia Injury Through TLR4/NF-κB and Keap-1/Nrf-2 Signaling Pathways

Abstract: Aims: Clinical application of cellular therapy for cardiac regeneration is significantly hampered by the low retention of engrafted cells, mainly attributable to the poor microenvironment dominated by inflammation and oxidative stress in the host's infarcted myocardium. This study aims at investigating whether liver X receptor (LXR) agonist T0901317 will improve survival of adipose-derived mesenchymal stem cells (AD-MSCs) after transplantation into infarcted hearts. Results: Noninvasive in vivo bioluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 42 publications
4
24
0
1
Order By: Relevance
“…Our results suggest that MSCs derived from the endometrium have greater therapeutic potential compared with cells derived from bone marrow or adipose tissue, the two most common sources of therapeutic MSCs , . We report stronger paracrine effects of EnMSC on cellular apoptosis and angiogenesis parameters in vitro and in vivo and greater myocardial salvage and enhanced cardiac function after MI in the EnMSC‐treatment groups.…”
Section: Discussionmentioning
confidence: 64%
“…Our results suggest that MSCs derived from the endometrium have greater therapeutic potential compared with cells derived from bone marrow or adipose tissue, the two most common sources of therapeutic MSCs , . We report stronger paracrine effects of EnMSC on cellular apoptosis and angiogenesis parameters in vitro and in vivo and greater myocardial salvage and enhanced cardiac function after MI in the EnMSC‐treatment groups.…”
Section: Discussionmentioning
confidence: 64%
“…Kuipers et al . found that T09, an LXR-α agonist, decreases AT1R and p38 MAPK in wild-type mice but not in LXR-α −/− mice1132. Therefore, the authors speculated that LXR-α plays a vital role in the positive feedback loop between the AT1R/p38 MAPK pathway and RAS.…”
Section: Discussionmentioning
confidence: 99%
“…263 Most recently, researchers reported that TLR3, the major TLR member that is responsible for the activation of IRF3 and IRF7, acted as a promoter of I/R-induced cardiac injury. 261, 264 Wang et al 265 also reported that the inactivation of TLR4/NF-κB and Keap-1/NRF-2 (nuclear factor, erythroid derived 2) signalings involved in liver X receptor-regulated cardiac repair and functional improvement post MI injury. According to immune signaling, the activation of TLRs may recruit adaptor proteins and may subsequently activate downstream factors to regulate the expression and function of IRFs, resulting in the induction of inflammatory and apoptotic responses.…”
Section: Upstream Irf Signaling In I/r Injurymentioning
confidence: 99%